Local Adaptive Thresholding Pada Preprocessing Citra Lontar Aksara Bali - Sutramiani, Ni Putu; Darmaputra, IKetut Gede; Sudarma, Made (Jurnal Teknologi Elektro; Vol 14 No 1 (2015): (January - June) Majalah Ilmiah Teknologi Elektro, 2015)
Balinesse lontar digitalization generates image file which acquired through a scanner or camera. Lontar image has noise because the results of the acquisition of the original lontar contained brown color that exist on the leaves. Therefore this paper focuses on improving the quality of the image to remove noise contained in the image by thresholding process. The method used in this paper is a Local Adaptive Thresholding. The test results in this paper generates the best image with the window (W)=70 and the threshold value (C)=0.05 which proved to remove noise at most of the few testing that has been done in this paper
Keywords: Lontar, scanner, noise, thresholding, local adaptive thresholding.